ANALISIS PERHITUNGAN PPH 21 TERHADAP GAJI KARYAWAN PADA PT INDO BISMAR DI SURABAYA - Deni Febrianto; Menur Kusumaningtyas (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Research on the analysis of Article 21 Income Tax (PPh 21) on employee salaries aims to understand the & application of PPh 21 on employee income. This involves calculating gross salaries, deducting job-related expenses and pension contributions, as well as calculating PPh 21 taxes. Errors in tax calculations can occur due to non-compliance with applicable laws and regulations. This research is conducted using a descriptive analytical approach with both primary and secondary data. The results of this study indicate that there are many errors in the updating of employee statuses according to current conditions. Consequently, errors occur in calculations, reported amounts, and overpayments of Article 21 Income Tax. The reporting of PPh 21 by PT. INDO BISMAR does not comply with applicable regulations. This occurs because the reported employee statuses are incorrect and affect tax calculations.